2020
DOI: 10.1016/j.jebo.2020.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The introduction of formal insurance and its effect on redistribution

Abstract: Transfers motivated by altruism, norms of giving, and guilt play an important role in supporting individuals who suffer losses due to risk. We present empirical evidence from an artefactual field experiment in Ethiopia in which we introduce formal insurance in a setting where donors make redistributive transfers to anonymously paired recipients. We find that donors reduce their transfers to recipients who don't take-up insurance, and that this effect is larger for donors who hold the ex ante belief that the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 58 publications
0
6
1
Order By: Relevance
“…With this study, we aimed to assess potential long-term consequences of introducing such formal insurance schemes to communities in which informal risk-sharing arrangements between smallholder farmers are prevalent. Since empirical studies have shown how diverse the transfer behavior of households can be after they have purchased insurance [19,[21][22][23][24][25][26], it is important to explicitly take transfer decisions into account when assessing the effectiveness of the combination of these risk-coping instruments. To systematically distinguish situations where formal insurance complements existing risk-sharing arrangements from situations in which harmful consequences on the resilience of smallholders emerge, we developed an agent-based model with formal and informal insurance options and combined this with social network analyses.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…With this study, we aimed to assess potential long-term consequences of introducing such formal insurance schemes to communities in which informal risk-sharing arrangements between smallholder farmers are prevalent. Since empirical studies have shown how diverse the transfer behavior of households can be after they have purchased insurance [19,[21][22][23][24][25][26], it is important to explicitly take transfer decisions into account when assessing the effectiveness of the combination of these risk-coping instruments. To systematically distinguish situations where formal insurance complements existing risk-sharing arrangements from situations in which harmful consequences on the resilience of smallholders emerge, we developed an agent-based model with formal and informal insurance options and combined this with social network analyses.…”
Section: Plos Onementioning
confidence: 99%
“…However, apart from direct positive effects, the introduction of formal insurance in communities where informal risk-coping instruments exist may have unintended side effects [18]. In lab-in-the-field experiments and household surveys covering different cultural contexts and insurance products, evidence has been found that formal insurance can crowd-out informal risk-sharing arrangements [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The second strand of literature is a series of experimental studies that investigate whether the introduction of voluntary formal insurance in developing countries has a crowding-out effect on informal mutual support (Landmann et al 2012;Lin et al 2014;Anderberg and Morsink 2020;Lenel and Steiner 2020) which is supported by their findings. 2 The experimental designs have in common that they exogenously expose participants to a risky outcome in one treatment, and allow them to reduce this level of risk exposure by choosing an insurance option in a second treatment.…”
Section: Introductionmentioning
confidence: 93%
“…Three recent articles complement the present paper by studying the opposite direction of causality. Using artefactual field experiments, Anderberg and Morsink (2020) and Lenel and Steiner (2020) vary the availability of insurance in Ethiopian and Cambodian settings, respectively, and study its impact on voluntary, non-reciprocal transfers. In a natural field experiment, Takahashi et al (2019) investigate the extent to which instrumented variation in demand for index insurance -varied in an encouragement design where discount coupons are distributed randomly -affects transfers among members of pre-existing informal risk-sharing groups of pastoralists in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental approach to studying such complex systems is to exogenously vary one part, and observe how the others respond. In this sense our approach is complementary to those ofAnderberg and Morsink (2020) andLenel and Steiner (2020), who vary the availability of insurance and study its effect on voluntary and non-reciprocal transfers.…”
mentioning
confidence: 99%